Gambaran Golongan Darah, Skrining Kadar Hemoglobin dan Infeksi Saluran Kemih Anak Usia Sekolah pada SDN 12 Biraeng Kabupaten Pangkajene Kepulauan - Apriani, Lita Paramitha; Muhiddin, Rachmawati A.; Widaningsih, Yuyun (Universitas Hasanuddin, 2025)
BACKGROUND: Permenkes has health efforts to ensure that school-aged children and adolescents receive health education through school and outside of school, so that every child can live a clean and healthy life, have healthy life skills, and good social skills so they can learn, grow and develop harmoniously and optimally to become qualified human resources. One of the school health efforts that can be done is screening for anemia, blood type, and urinary tract infection. METHODS: This research is a descriptive observational study using a sample of 4th to 6th-grade students. RESULTS: Of the 93 subjects, 37 (40%) were male and 56 (60%) were female. The mean age of the patients was 10.2 years with a standard deviation of 1.057 years and an age range of 9-12 years. A total of 36 (38%) children had blood type O, 26 (28%) had blood type B, 22 (24%) had blood type A, and 9 (10%) had blood type AB. Subjects who experienced anemia were 12 (13%) and those who experienced UTI were 9 (10%). CONCLUSION: The blood type of students at SDN 12 Biraeng is dominated by blood type O and it was found that 13% of students had anemia and 10% of students had urinary tract infections.